Specific model for the estimation of methane emission from municipal solid waste landfills in India. (September 2016) - Kumar, Sunil; Nimchuk, Nick; Kumar, Rakesh; Zietsman, Josias; Ramani, Tara; Spiegelman, Clifford; Kenney, Megan
Highlights: A modelling tool for CH4 emission from landfills developed for Indian condition. CH4, CO2, O2 and temperature were the prime factors for development of the model. The developed model was validated for three landfill sites in India. Abstract: The landfill gas (LFG) model is a tool for measuring methane (CH4 ) generation rates and total CH4 emissions from a particular landfill. These models also have various applications including the sizing of the LFG collection system, evaluating the benefits of gas recovery projects, and measuring and controlling gaseous emissions. This research paper describes the development of a landfill model designed specifically for Indian climatic conditions and the landfill's waste characteristics. CH4, carbon dioxide (CO2 ), oxygen (O2 ) and temperature were considered as the prime factor for the development of this model. The developed model was validated for three landfill sites in India: Shillong, Kolkata, and Jaipur. The autocorrelation coefficient for the model was 0.915, while the R 2 value was 0.429.